2018
DOI: 10.1371/journal.pone.0196534
|View full text |Cite
|
Sign up to set email alerts
|

Useful field of view test performance throughout adulthood in subjects without ocular disorders

Abstract: Previous research has shown an age-related decline in Useful Field of View (UFOV) test performance, which measures the duration required to extract relevant information from a scene in three subtasks. However, these results are mostly based on data that may have been confounded by (age-related) ocular diseases. We examined UFOV performance in subjects aged 19.5 to 70.3 years to investigate how UFOV performance changes throughout adulthood. All subjects underwent a thorough ophthalmological examination to exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…Indeed, a floor effect has been reported for healthy participants in the past. 21,36,37 Yet, whereas healthy control participants in our study all reached the lowest, that is, best score, some patients did not. Furthermore, patients who were not included in the analyses because they were unable to finish all three iUFOV subtests did show reduced performance on this subtest.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Indeed, a floor effect has been reported for healthy participants in the past. 21,36,37 Yet, whereas healthy control participants in our study all reached the lowest, that is, best score, some patients did not. Furthermore, patients who were not included in the analyses because they were unable to finish all three iUFOV subtests did show reduced performance on this subtest.…”
Section: Discussioncontrasting
confidence: 62%
“…However, we did not have age-corrected measures available for the iUFOV or adapted NEI VFQ-25, which are also affected by age. 36 , 37 , 45 , 46 We, therefore, calculated an uncorrected HFA score based on the raw visual sensitivity scores of the entire visual field for both eyes. To correct for age, we matched our patient and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the established literature demonstrating the utility of UFOV as a predictor of driving performance and the evidence that it may improve driver reaction time, we elected to include the UFOV version 7 as an additional mid-level transfer outcome measure of 3D-MOT training. This version of the test (described in in detail by Woutersen et al ( 2018 )) is composed of three subtests that measure, respectively, (1) processing speed, (2) processing speed under a divided attention condition and, finally, (3) processing speed under a selective attention condition. To date, no study has demonstrated transfer of 3D-MOT training to UFOV performance in healthy older adults.…”
Section: Methodsmentioning
confidence: 99%
“…One significant outlier in the control group was identified using boxplots of pretraining UFOV scores and removed from subsequent analyses (following [ 19 ]). We added participants’ UFOV scores across all three subtests as young adults tend to exhibit floor effects 1 with very little variability on the first two subtests [ 20 ], and conducted statistical analyses on total UFOV scores after confirming that this aggregate measure did not violate the assumption of normality. To compare post-training 3D-MOT, UFOV and perceptual discrimination task improvement between both groups, we conducted a univariate analysis of covariance tests with pretraining scores entered as a covariate (following recommendations of [ 21 ]).…”
Section: Methodsmentioning
confidence: 99%